2019
DOI: 10.1111/pcn.12936
|View full text |Cite
|
Sign up to set email alerts
|

Toward the establishment of neurophysiological indicators for neuropsychiatric disorders using transcranial magnetic stimulation‐evoked potentials: A systematic review

Abstract: Transcranial magnetic stimulation (TMS) can depolarize the neurons directly under the coil when applied to the cerebral cortex, and modulate the neural circuit associated with the stimulation site, which makes it possible to measure the neurophysiological index to evaluate excitability and inhibitory functions. Concurrent TMS and electroencephalography (TMS-EEG) has been developed to assess the neurophysiological characteristics of cortical regions other than the motor cortical region noninvasively. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 146 publications
(363 reference statements)
0
18
0
Order By: Relevance
“…Collectively, these findings suggest parts of the therapeutic mechanisms of 1Hz-rTMS to the right DLPFC for depression. Lastly, the present study warrants future research that investigates the neurophysiological effects of various types of TMS treatment, providing unique and informative perspectives on the pathophysiology underlying neuropsychiatric disorders as represented by major depressive disorders and schizophrenia [55].…”
Section: Discussionmentioning
confidence: 90%
“…Collectively, these findings suggest parts of the therapeutic mechanisms of 1Hz-rTMS to the right DLPFC for depression. Lastly, the present study warrants future research that investigates the neurophysiological effects of various types of TMS treatment, providing unique and informative perspectives on the pathophysiology underlying neuropsychiatric disorders as represented by major depressive disorders and schizophrenia [55].…”
Section: Discussionmentioning
confidence: 90%
“…An electroencephalogram (EEG) is the sum of postsynaptic potentials in the cerebral cortex, which can reflect the overall functional state of the electrophysiological activity of the cranial nervous system with high sensitivity. [ 36–38 ] Degenerative cholinergic neurons and decreased acetylcholine content in the synaptic cleft have been shown to lead to changes in synaptic potential. [ 36,37,39 ] Synaptic potential synchronization disorder presents as an increase of low‐frequency θ waves.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, these methodological differences in the included studies make it difficult to interpret the results. Hence, future research applying more standardized experimental methods with larger sample sizes in a transdiagnostic approach will help improve the quality of TMS-EEG study [ 89 ] and further such sophisticated TMS-EEG research will be important to replicate and confirm the currently available findings of this special modality [ 17 ]. In addition, previous TMS-EEG studies have reported TMS neurophysiological findings in patients with SCZ at various clinical stages, but it remains unclear at which clinical stage of SCZ these abnormal neurophysiological findings occur and how they progress.…”
Section: Discussionmentioning
confidence: 99%
“…However, on the other hand, recent meta-analysis studies have shown inconsistencies in the findings of these MRS findings [ 15 , 16 ]. One way to address these limitations is the development of a combined transcranial magnetic stimulation (TMS) and electroencephalography (EEG) technique that can non-invasively assess the neurophysiological properties of the human cerebral cortex [ 2 , 3 , 17 ].…”
Section: Introductionmentioning
confidence: 99%